Evaluating the FACIT-Sp-12: a systematic review of measurement properties of spiritual well-being in cancer patients - Fauji, Achmad; Wijoyo, Eriyono Budi; Ninik Yunitr; Imami Nur Rachmawati; Yati Afiyanti (Universitas Airlangga, 2025)
Introduction: This study aims to investigate whether the FACIT-Sp-12's measurement properties yield the most accurate spiritual data for cancer patients. Methods: This systematic review examined full-text studies written in English and involving patients with cancer published between 2000 and 2024, using cross-sectional, randomized controlled trials, case-control, and quasi-experimental designs. This study used the MEDLINE (PubMed and EBSCO), ScienceDirect, Scopus, Taylor and Francis, and selected ProQuest databases. We assessed the papers methodically using the PRISMA flow before reviewing ten of them. The Consensus-based Standards for the Selection of Health Measurement Instruments tool has been used for evaluating the review articles. Results: We found that various studies on spirituality in cancer patients conducted in different countries have employed diverse research methods. All these studies used the FACIT-Sp-12, which has been modified and adapted for cultural contexts. Cronbach's alpha ranges from 0.70 to 0.91, indicating that FACIT-Sp-12 is consistent across studies. COSMIN has been used to evaluate and critique FACIT-Sp-12; however, its structural validity, Cronbach's alpha for the subscales, intraclass correlation, and measurement error remain unsatisfactory. Some publications examine hypotheses and provide satisfactory responses, but there is little discussion on criterion validity or cross-cultural adaptation. Conclusions: We determined that patients with cancer could use the FACIT-Sp-12. This study suggests using the FACIT-Sp-12 spiritual assessment tool for cancer patients in research and nursing care.